2022
DOI: 10.1371/journal.pone.0262667
|View full text |Cite|
|
Sign up to set email alerts
|

Urine peptidome in combination with transcriptomics analysis highlights MMP7, MMP14 and PCSK5 for further investigation in chronic kidney disease

Abstract: Chronic kidney disease (CKD) is characterized by the loss of kidney function. The molecular mechanisms underlying the development and progression of CKD are still not fully understood. Among others, the urinary peptidome has been extensively studied, with several urinary peptides effectively detecting disease progression. However, their link to proteolytic events has not been made yet. This study aimed to predict the proteases involved in the generation of CKD-associated urinary excreted peptides in a well-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
(76 reference statements)
2
7
0
Order By: Relevance
“…Consistent with previous findings, we identified genes known to have a significant role in the pathogenesis of ADPKD including WNT7A, LCN2, and MMP7 (Additional files 4 and 5 ; Data files “deseq2_outputs”) (Li et al 2018 ; Petra et al 2022 ; Viau et al 2010 ; Wilk et al 2023 ; Zhou et al 2017 ). The previously noted biomarkers of CKD progression LCN2 and MMP7 were upregulated in both P28 and P21 cystic data sets (Petra et al 2022 ; Viau et al 2010 ; Zhou et al 2017 ). In line with other studies, most of the upregulated pathways in the cystic data sets P21 and P28 were associated with inflammation, leukocyte activity, NAD + activity, and cytokine response.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous findings, we identified genes known to have a significant role in the pathogenesis of ADPKD including WNT7A, LCN2, and MMP7 (Additional files 4 and 5 ; Data files “deseq2_outputs”) (Li et al 2018 ; Petra et al 2022 ; Viau et al 2010 ; Wilk et al 2023 ; Zhou et al 2017 ). The previously noted biomarkers of CKD progression LCN2 and MMP7 were upregulated in both P28 and P21 cystic data sets (Petra et al 2022 ; Viau et al 2010 ; Zhou et al 2017 ). In line with other studies, most of the upregulated pathways in the cystic data sets P21 and P28 were associated with inflammation, leukocyte activity, NAD + activity, and cytokine response.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous findings, we identified genes known to have a significant role in the pathogenesis of ADPKD including WNT7A, LCN2, and MMP7 (Data files "deseq2_outputs"). (35,40,(68)(69)(70) The previously noted biomarkers of CKD progression LCN2 and MMP7 were upregulated in both P28 and P21 cystic data sets. (68-70) Additionally, we also found that Wnt7a, previously characterized for its role in WNT signaling in Pkd2-/-cells, was upregulated in both cystic datasets (P28 and P21).…”
Section: Discussionmentioning
confidence: 86%
“…Differentially expressed genes (upregulated by TGF-β but downregulated in KO5 MMC), such as Xylt1 (Tziastoudi et al, 2020), Pcsk5 (Petra et al, 2022), and Ap1s2 (Woroniecka et al, 2011;Zhong et al, 2013;Gong et al, 2016), also showed similar patterns in ATAC and H3K27ac (Supplementary Figure S7). Nlrx1 (related to mitochondrial immunity and inflammation) (Moore et al, 2008;Tattoli et al, 2008;Arnoult et al, 2009;Nagai-Singer et al, 2019) showed significantly lower expression and ATAC-peaks in KO5 MMC (Supplementary Figure S8).…”
Section: Frontiers In Molecular Biosciencesmentioning
confidence: 81%